THE CONTRIBUTION OF ISLAMIC SPIRITUAL EXTRACURRICULAR ACTIVITIES AND SCHOOL ENVIRONMENTAL SUPPORT IN THE FORMATION OF STUDENTS' SPIRITUAL INTELLIGENCE - Agus Supriyadi; Mohamad Aso Samsudin; Eriyanto Eriyanto (Lisan Al-Hal: Jurnal Pengembangan Pemikiran dan Kebudayaan)
Spiritual intelligence is essential for students in this generation because it influences the development of attitudes such as values, morality, and self-awareness. This study investigates how extracurricular activities like Dhuha prayer, Islamic studies, princesses, and others might enhance students' educational experiences by developing their spiritual intelligence. This study employs qualitative methodologies with a descriptive-analytic methodology. Thus, the researcher will explore the field to see how spiritual activities occur at Junior High School 1 Asembagus. The researcher's data-gathering approaches include observation, interviews, and documentation. The researcher's data-gathering approaches include observation, interviews, and documentation. According to the findings of this study, teachers implement Islamic spiritual extracurricular activities and school environmental support in the form of spiritual activities in the school environment, and students participate in daily, weekly, and annual activities, encouraging students to be more obedient in worship, carry out religious commands, and avoid His prohibitions. Enhancing their piety, faith, and tolerance and teaching them decent manners. This practice not only makes youngsters more religious, but it also helps them behave better in ordinary situations.